Priority Competencies Needed by UF/IFAS Extension County Faculty - Amy Harder (EDIS)
Research shows that competency is a better indicator of employee potential than intelligence alone. This 5-page fact sheet outlines ten competency areas relevant to Extension county faculty, as well as examples of how Extension faculty might embody these qualities in their work. Written by Amy Harder, and published by the UF Department of Agricultural Education and Communication, September 2015.